LOOKING AT THE ACTIVITIES OF CULTURAL CENTERS: PROVIDING CULTURAL CENTERS WITH QUALIFIED STAFF - Maratova , Nilufar Laziz qizi; Xolmoʻminov, Moʻminmirzo (Educational Research in Universal Sciences, 2022)
The article describes in detail the role of cultural centers in our lives, their activities, tasks, as well as the opportunities and conditions created to bring our centers to a new level, the issues of attracting qualified personnel to cultural centers. Suggestions and comments were made on the issues that need to be addressed in order to expand the activities of cultural and art institutions, to promote our national culture among the population, to organize meaningful leisure time for young people, to strengthen the attention of our people to our culture and art. The relationship between the staff and the manager at the centers describes the need to approach problems with modern methods and innovative ideas.